Narali Purnima marks the end of the monsoon season - Mumbai Archive Project Team (Jio Institute, 2024)
Narali Purnima marks the end of the monsoon season and the beginning of the new fishing season, which is of significant importance for Kolis and other fishing communities dependent on the sea for their livelihood.